EFFECTS OF DIFFERENT DOSES OF SHIITAKE MUSHROOM (LENTINUS EDODES) ON SPERM PARAMETERS AND TESTICULAR TISSUE IN RATS: AN EXPERIMENTAL STUDY - B. Büyük; N. Demir; H. A. Eroğlu; Ö. Öztopuz (Journal of Animal and Plant Sciences, 2023)
Lentinus edodes has been cultivated and used as food and medicine in far eastern countries.The present study aimed to reveal whether L.edodes that is used for different purposes has a toxic effect on the male genital system and to investigate its relationship with male infertility by showing its effects on sperm parameters. Twenty-four male Wistar rats were randomly divided into three groups as Control (C), Low-dose (LD) and High-dose (HD). Rats in Control were administered saline physiological once a day for 7 days. The LD and HD groups received 100 and 400mg/kg of L.edodes extract, respectively, once daily for 7 days. At the end of 7 days of administration of treatments, semen analysis, micronucleus analysis, gene expression levels and testicular Johnsen scoring was performed. Comparisons between groups without normal distribution were analyzed using Kruskal–Wallis variance analysis and those between groups with normal distribution were analyzed using one-way analysis of variance, followed by Tukey’s test. P values of <0.05 were considered statistically significant. It is demonstrated that both low and high doses of extract significantly reduced spermatogenesis in seminiferous tubules found in the testicles of rats. In addition, high-dose administration resulted in decreased total sperm counts, whereas the progressive and non-progressive sperm motility counts were significantly decreased in both experimental groups. The gene expression levels of Casp-3 and TNF-α were increased in both the LD and HD groups compared with that in the C. Oral administration of low and high doses of L.edodes led to reduced spermatogenesis in the testicles, tissue damage to the testicle and decreased motile and total sperm counts.
Keywords: Infertility; Lentinus edodes; Male Rat; Shiitake mushrooms; Testis